PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BANTEN TAHUN 2019-2021 - Bagas Fakhri Maulana; Muhammad Farhan; Deris Desmawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
Human Development Index or HDI and Economic Growth in the Regency/City of Banten Province needsto be studied whether the Human Development Index and Economic Growth have influence or not. the studied variable are Independent Variable HDI and Dependent Variable Economic Growth . The research methods used is quantitative method using document data from Central Statistics Agency (CSA) with some literature review. The result showed that HDI had no significant effect on Economic Growth. Where if there is a decrease in the Human Development Index, it can’t be confirmed that it will reduce Economic Growth in Banten Province. Keywords: HDI, Economic Growth, Banten